Your honor. Season two [videorecording (DVD)] - Moffat, Peter, 1962- (Showtime : CBS DVD, 2023)
Emmy and Golden Globe-winner Bryan Cranston ("Breaking Bad") returns in the explosive second season of Your Honor. Disbarred, disgraced, and all but destroyed, ex-judge Michael Desiato is offered a ray of hope when a federal agent recruits him to take down the empire of corruption and vengeance that runs New Orleans.